Jitteriness/anxiety syndrome caused by coadministration of celecoxib, a selective COX‐2 inhibitor, with escitalopram and trazodone in a patient with depression and spondylolisthesis - Toshinori Shirata; Shinji Yano; Keisuke Noto; Muneaki Kanno; Akihito Suzuki (Wiley, 2023)
Abstract Antidepressant‐induced jitteriness/anxiety syndrome is characterized as anxiety, agitation, panic attacks, insomnia, irritability, hostility, aggressiveness, impulsivity, akathisia, and (hypo)mania, which appear immediately after initiation or increased dosage of an antidepressant. This report describes a case of the jitteriness/anxiety syndrome caused by the coadministration of celecoxib with escitalopram and trazodone in a patient with depression and spondylolisthesis. The depression of a patient, a woman in her 60 s, had been in remission at least for 5 years under treatment using escitalopram and trazodone. Immediately after coadministration of celecoxib because of her buttock and limb pain, she showed anxiety, agitation, akathisia, insomnia, irritability, aggressiveness, impulsivity, and hypomania. These symptoms disappeared after the discontinuation of celecoxib. The present case suggests that coadministration of celecoxib with escitalopram and trazodone can cause the jitteriness/anxiety syndrome, presumably via a pharmacokinetic interaction of celecoxib with these antidepressants and/or the effects of celecoxib on serotonergic neurotransmission.